Perceptual-Load-Induced Selection as a Result of Local Competitive Interactions in Visual Cortex. - Torralbo, Ana; Beck, Diane M. (Psychological Science., 2008)
A study investigated whether visual cortex cell interactions that represent nearby stimuli determine the perceptual load of a task and whether manipulating competitive spatial interactions should modulate distractor processing. Findings revealed that either spatially separating the task-relevant items in a display or positioning the target and nontargets in different visual fields increased interference from a distractor that was to be disregarded. Findings supported the idea that the capability to ignore such distracting information results to some extent from the need to actively resolve competitive interactions in visual cortex and is not the outcome of an exhausted capacity per se.